Mortalidade no trânsito, desenvolvimento econômico e desigualdades regionais no Brasil - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This work aims to study socioeconomic variables related to mortality rates from traffic accidents in Brazil, investigating the effect of economic development and important factors that explain the differentiation of traffic deaths between Brazilian states. It was observed that a higher percentage of motorcycles greatly increases mortality in the states. In the opposite direction, an increase in police force and a larger population reduces this rate in Brazilian states. Increasing income also has an effect on increasing deaths, although in richer states this effect is opposite. In the poorest states, road improvements have an upward impact on the mortality rate, due to the current poor state of road conservation, which reduces the energy of accidents and consequently traffic deaths.
Keywords: R41; 330; traffic mortality; transit accidents; road safety